Management Audit to Evaluate the Economical, Efficiency, and Effectiveness of Purchasing Function in GK Hotel - Ni Putu Yasinta Oktavia Darnata; I M M Arsana; A A P Suardani (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
This research examines the economic, efficiency, and effectiveness of purchasing function and reveals findings obtained during the implementation of a management audit to give appropriate recommendations for better company performance in the future. The analytical techniques used in this research are quantitative and qualitative analytical techniques. The data analysis results in 2017-2019 show that the highest rate of economics occurred in 2019. The highest efficiency rate occurred in 2019 and declining the effectiveness rate in 2019. That is due to obstacles in the purchasing function resulting in wastage. These obstacles are the weaknesses in unauthorized purchase request activities, purchasing goods that did not comply with order specifications, and the delay of payment to the supplier due to a lack of funds from the head office. This research concludes that the economic rate in 2019 is uneconomical, the efficiency of purchase costs in 2019 is inefficient, and the effective rate in 2019 is quite effective. The recommendation is to make a payment agreement with the supplier, tighten the process of purchasing requests, and control in making the article description.